Optimization of Cap Rajawali Bean Bread Production Capacity Using Goal Programming Method with Priority - Angie Maretha Rajagukguk (PT FORMOSA CENDEKIA GLOBAL, 2022)
Roti Kacang Cap Rajawali is a company that produces peanut bread with various flavors such as green beans, black beans, pineapple beans, chocolate beans, and others. Rajawali peanut bread has more than one target to achieve, namely minimizing raw material costs, maximizing processing time, maximizing revenue, maximizing production results and determining the optimal amount of production. Therefore the company needs a method that can be used in the multi-objective problem of Rajawali Bean Bread Company. The Goal Programming method is the right method to use for company problems. Based on the data analysis that has been carried out by researchers with the help of LINDO software in the data processing, more profitable results are obtained compared to the methods that have been implemented by the company so far.